The USA in the making of the USSR : the Washington Conference, 1921-1922, and "uninvited Russia" - Dukes, Paul, 1934- (RoutledgeCurzon studies on the history of Russia and Eastern Europe, 2004)
The USA's contribution to the making of the USSR was accidental. In the belief that the Russian Socialist Federative Soviet Republic could not survive, American statesmen strove to keep the former Tsarist empire intact for a non-communist successor regime in the face of attempts by other powers to carve out spheres of influence in both European and Asiatic Russia. In this manner, they unwittingly facilitated the formation of the Union of Soviet Socialist Republics. This book shows the importance of the 'Russian question' at the Washington Conference and throws light on the emergence of.